Arrhythmogenic Effects of Cardiac Memory. Issue 15 (11th October 2022) - Viskin, Sami; Chorin, Ehud; Schwartz, Arie Lorin; Kukla, Piotr; Rosso, Raphael
Abstract : Cardiac memory is the term used to describe an interesting electrocardiographic phenomenon. Whenever a QRS complex is wide and abnormal, such as during ventricular pacing, the T waves will also be abnormal and will point to the opposite direction of the wide QRS. If the QRS then normalizes, such as after cessation of ventricular pacing, the T waves will normalize as well, but at a later stage. The period of cardiac memory is the phase between the sudden normalization of the QRS and the eventual and gradual return of the T waves to their baseline morphology. Cardiac memory is assumed to be an innocent electrocardiographic curiosity. However, during cardiac memory, reduction of repolarizing potassium currents increases left ventricular repolarization gradients. Therefore, when cardiac memory occurs in patients who already have a prolonged QT interval (for whatever reason), it can lead to a frank long QT syndrome with QT-related ventricular arrhythmias (torsades de pointes). These arrhythmogenic effects of cardiac memory are not generally appreciated and are reviewed here for the first time.